1994
DOI: 10.1093/jn/124.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Propionic Acid and Bile Acid Excretion in the Hypocholesterolemic Effects of Oligosaccharides in Rats

Abstract: The aim of this study was to evaluate the influence of dietary propionic acid and bile acid excretion on the hypocholesterolemic effect of fibers. For this purpose, rats were adapted to a diet containing 10 g inulin, 10 g beta-cyclodextrin, or 2.5 g calcium propionate per 100 g diet. Both the inulin and beta-cyclodextrin diets elicited high propionic acid fermentations in the cecum (approximately 45% of total short-chain fatty acids) with relatively low molar proportions of acetic and butyric acids. In rats fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 31 publications
1
87
3
Order By: Relevance
“…Supplementation with inulin has also been shown to increase bile acid secretion in rats (Levrat et al, 1994) and in hamsters (Trautwein et al, 1998).…”
Section: Changes In Faecal Metabolites and Enzyme Activitymentioning
confidence: 99%
“…Supplementation with inulin has also been shown to increase bile acid secretion in rats (Levrat et al, 1994) and in hamsters (Trautwein et al, 1998).…”
Section: Changes In Faecal Metabolites and Enzyme Activitymentioning
confidence: 99%
“…Anderson (1985) suggested that increased hepatic propionate supply via the portal vein from large-bowel NSP fermentation may inhibit hydroxymethylglutaryl-CoA reductase, the rate-limiting enzyme for cholesterol biosynthesis (Rodwell et al 1976;Levrat et al 1994), and thus reduce circulating cholesterol concentrations. There is no doubt that increased consumption of fermentable NSP has been associated with increased caecal production of SCFA, and higher concentrations of SCFA, including propionate, in portal blood (Goodlad & Mathers, 1990).…”
Section: Hypocholesterolaemic Effects Of Nsp Sourcesmentioning
confidence: 99%
“…While b -CD is not hydrolyzed by the salivary or pancreatic a -amylase (Andersen et al 1983;Suzuki and Sato 1985), it is fermented in mammalian large intestine to glucose and oligosaccharides by resident micro ora (Suzuki and Sato 1985;Levrat et al 1994) and humans (Flourie et al 1993;Antenucci and Palmer 1984). b -CD is negligibly hydrolyzed in and slightly absorbed from the stomach and small intestine (Andersen et al 1983;Antenucci and Palmer 1984;Flourie et al 1993).…”
Section: Introduction To Cyclodextrinsmentioning
confidence: 99%
“…This favors hypocholesterolemia (Riottot et al 1993;Levrat et al 1994). b -CD is fermented mainly to propionate in the large intestine (Levrat et al 1994;Moundras et al 1994).…”
Section: Introduction To Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation